Developing a scale for value co-creation in producer-supplier relationships - Mehmet Ali Zengin; Mustafa Kemal Yilmaz (Future Business Journal)
Abstract This study aims to develop an original VcC scale in manufacturer-supplier relationships in industrial markets. Qualitative and quantitative methods were used in the study. The researchers first reviewed the scale development processes in the literature, and they utilized a five-stage scale development process. The original scale was developed by inductive and deductive methods. In the deductive method, similar scale items in the literature were examined and added to the item pool. In the inductive method, as a result of interviews with experts working in industrial markets, additions were made to the item pool. Following the fulfillment of all presumptions and analysis of the data, it was discovered that the initial version of the VcC scale comprised three dimensions and sixteen items related to supplier-manufacturer relationships in the machinery manufacturing industry. These dimensions are process development, information sharing and interaction. The three-dimensional scale explains 57.56% of the total variance. The originality of this study lies in the development of an advanced and detailed scale that determines how value co-creation (VcC) can be established in manufacturer-supplier relationships within the machine manufacturing industry, which holds strategic importance in industrial markets.